Pengaruh Penggunaan Strategi Critical Incident Terhadap Motivasi Belajar pada Mata Pelajaran Akidah Akhlak di Kelas VIII MTsN 5 SOLOK SELATAN - Resti Rahayu; Wedra Aprison; Supriadi Supriadi; Nurhasnah (STIKes Ibnu Sina Ajibarang, 2023)
This study was backed by a teacher who implemented a critical-incident-based active-learning strategy in the context of moral-based education. However, it is still visible that some students are unmotivated throughout the learning-teaching process, that some students are less active during class, and that some students would rather gossip about one another than pay attention in class. The purpose of this study was, therefore, to determine whether or not the use of critical event strategy had any effect on the students' motivation to learn akidah akhlak in the eighth grade at MTsN 5 Solok Selatan. This type of research is similar to the correlative ex post facto research. Participants in this study, a total of 115 students, were all in Grade 8. Cluster random sampling was used for this study's data collection. There were a total of 34 students who used the pen. Data collection was accomplished using the questionnaire technique. However, academics conduct preliminary tests for normality and linearity before the more advanced tests for hypothesis testing. Next, we'll run a coefficient determinant to see how much of an impact independent variables have on dependent ones. According to the research that has been done so far, the critical incident strategy has an impact on student motivation for learning of 36.3%, while the remaining 63.7% is determined by other factors. The findings of this study indicate that the use of critical event strategy has a significant impact on the students' motivation to learn akidah akhlak in class at the eighth grade level of MTsN 5 Solok Selatan..